The impact of board characteristics on firm performance: Evidence from nonfinancial listed companies in Kuwaiti Stock Exchange - Al-Matari, Ebrahim Mohammed; Al-Swidi, Abdullah Kaid; Fadzil, Faudziah Hanim; Al-Matari, Yahya Ali (Macrothink Institute, 2012)
The core aim of this study is to examine the relationship between board characteristics and the firm performance of non-financial listed Kuwaiti firms.To achieve the objectives of the study, the data were collected from a sample of 136 companies for the financial year 2009.Variables such as CEO duality, COE tenure, audit committee size, board size and board composition were considered as predictors of the firm performance that was measured employing the return on assets (ROA).By contrast, the effects of CEO tenure and leverage on firm performance were found to be negative and significant at the chosen level of significance.To test the hypotheses of the study, multiple linear regression analysis using SPSS 18.0 was utilized.Using the firm size and leverage as a control variable, the findings of the study support the positive effects of CEO duality and audit committee size on ROA.Other findings of the study were discussed in the discussion section and some other future study directions were provided.